Progress and Challenges of Biological Leaching of Heavy Metal in Coal Ash from a Power Plant - Yuni Lisafitri; Edwan Kardena (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Bioleaching is a technique for reducing the heavy metal content of coal ash by using bacteria, fungi, or yeast. Previous studies in heavy metal bioleaching of coal ash discussed the factors affecting the process, but as yet there is little information on the challenges of using microorganisms. Therefore, this study aimed to obtain comprehensive information regarding the use of microorganisms in heavy metal bioleaching. Heavy metal concentrations in coal ash are low, and the metals are diverse. The components of coal ash are complexes that cannot leach certain heavy metals according to previous studies. These low concentrations and complex components make it difficult to investigate the bioleaching mechanism. The combination of biological and chemical interactions involves various components in this system. The high concentration of iron and heavy metal leached could be toxic for microorganisms. The process is influenced by several factors, such as particle size, pH, and pulp density. Most heavy metal bioleaching studies on coal ash have been conducted on a small scale to control conditions affecting the process. Bioleaching kinetics in coal is a liquid-solid reaction that can be represented by the shrinking core model, which was mainly used in this study.